Gene Expression-Based Signature Can Predict Sorafenib Response in Kidney Cancer - Gudkov, Alexander; Shirokorad, Valery; Kashintsev, Kirill; Sokov, Dmitriy; Nikitin, Daniil; Anisenko, Andrey; Borisov, Nicolas; Sekacheva, Marina; Gaifullin, Nurshat; Garazha, Andrew; Suntsova, Maria; Koroleva, Elena; et al. (Frontiers in Molecular Biosciences, 2022)
Sorafenib is tyrosine kinase inhibitory drug with multiple molecular specificities that is approved for clinical use in second line treatments of metastatic and advanced renal cell carcinomas (RCCs). However, only 10-40% of RCC patients respond on sorafenib-containing therapies, and personalization of its prescription may help finding an adequate balance of clinical efficiency, cost effectiveness, and side effects. We investigated whether expression levels of known molecular targets of sorafenib in RCC can serve as prognostic biomarker of treatment response. We used Illumina microarrays to profile RNA expression in pre-treatment formalin-fixed paraffin-embedded (FFPE) samples of 22 metastatic or advanced RCC cases with known responses on next-line sorafenib monotherapy. Among them, 9 patients showed partial response (PR), 3 patients - stable disease (SD), and 10 patients - progressive disease (PD) according to Response Evaluation Criteria In Solid Tumors (RECIST) criteria. We then classified PR+SD patients as “responders”, and PD patients as “poor responders”. We found that gene signature including eight sorafenib target genes was congruent with the drug response characteristics and enabled high-quality separation of the responders and poor responders (Area Under a receiver operating characteristic Curve AUC 0.89). We validated these findings on another set of 13 experimental annotated FFPE RCC samples (for 2 PR, 1 SD, and 10 PD patients) that were profiled by RNA sequencing and observed AUC 0.97 for 8-gene signature as the response classifier. We further validated these results in a series of qRT-PCR experiments on the third experimental set of 12 annotated RCC biosamples (for 4 PR, 3 SD, and 5 PD patients), where 8-gene signature showed AUC 0.83.